Image Compression Schemes Incorporating Modified Contrast Sensitivities of Human Visual System - Humaidan, Raghad Abdualemam (Journal of engineering sciences and information technology, 2022)
This paper deals with the importance of working on image compression, which is reduce the number of bits needed to represent an image while maintaining a desirable quality. This is done by eliminating data that are visually unnecessary and taking advantage of redundancy that is inherent in most images.Image compression plays a critical role in telemetric applications. Image compression involves reducing the typically massive amount of data to represent an image. This is done by eliminating data that are visually unnecessary and taking advantage of redundancy that is inherent in most images. It is desired that either single image or sequences of images be transmitted over computer networks at large distances so as that they could be used for a multitude of purposes. Image compression is essential for applications such as transmission and storage in databases. It aims to reduce the bit rate for transmission or storage while maintaining an acceptable fidelity or a good image quality.
Keywords: PSNR; DWT; HVS; CSF; JPEG2000; PIXEL; bpp; wavelet; masking